Influence of sulphur and bio-regulators on growth, yield and oil content of cumin (Cuminum cyminum) - MEHRIYA, MOTI LAL; GEAT, NEELAM; SARITA, SARITA (The Indian Journal of Agricultural Sciences, 2022)
Sulphur and bio-regulators influence various physiological and biochemical activities inside the plant. The present study aimed to evaluate the effect of sulphur and bio-regulators (ascorbic acid, thioglycolic acid and salicylic acid) on growth, yield and essential oil content in cumin (Cuminum cyminum L.). A field experiment was conducted during rabi 2013â€“14, 2014â€“15 and 2015â€“16 at Agricultural Research Station, Mandor (Agriculture University, Jodhpur). Factorial randomised block design with three replications was used. Four levels of sulphur (0, 15, 30 and 45 kg/ha) and four sprays of bio-regulators (Ascorbic acid, TGA and salicylic acid) @100 ppm at vegetative and flowering stage were applied. Pooled data revealed that application of sulphur @45 kg/ha significantly increased number of branches/plant, plant height (cm), number of umbels/plant, umbelletes/umbel, seeds/umbellete, test weight and also seed yield over control. Foliar application of bio-regulators @100 ppm at vegetative and flowering stage significantly increased the seed yield and oil content of cumin. The highest net return ` 93250 and benefit: cost ratio 3.32) was observed on application of sulphur @45 kg/ha followed by thioglycolic acid (net return ` 86120/ha, B:C ratio 3.12). Thus, we can recommend the application of sulphur and TGA bioregulator to the farmers in western arid zone for doubling the farmers’ income in a sustainable way.